(untitled) (INNOTEC, 2012)
The aim of this development is to add value to one of the by-products of the poultry slaughtery, the chicken’s feet. The process began with the skinning of the chicken’s feet, which underwent a tanning process to obtain a leather characterised for its similarity with exotic leathers such as the reptile ones. To facilitate its possible production by artisanal means we designed a more environmental-friendly process, eliminating the use of sodium sulfide in the stages corresponding to dehairing and liming, followed by a chromium-free tanning based on a combination of vegetable tannins and synthetic retanning agents. Confirmation of the tanning of the skins was performed by measuring the shrinkage temperature of leathers, obtaining a value of 80 °C, higher than those of the raw hides. Physical properties were evaluated to characterize the product, obtaining tensile strength values of 0,65 kg/mm2 and a tear resistance of 2,10 kg/mm.